Nanosilicon alters oxidative stress and defence reactions in plants: a meta-analysis, mechanism and perspective. Issue 10 (22nd August 2022) - Fan, Ningke; Zhao, Chunjie; Yue, Le; Ji, Haihua; Wang, Xie; Xiao, Zhenggao; Rasmann, Sergio; Wang, Zhenyu
Abstract : The main goal of this work was to quantify and explore the variation of nanosilicon-mediated effects on the mitigation of oxidative stress in plants against abiotic and biotic stress. Abstract : Alleviating the adverse effects of abiotic and biotic stress factors on crop plants is essential to achieve higher productivity for satisfying the future food demands of the rapidly-growing global human population. The application of Si nanomaterials (Si NMs) could be an ecologically-sound alternative, as there is evidence that Si NMs could positively mitigate oxidative stress in plants. However, not all studies report clear positive effects of Si NM amendment, suggesting a high level of context-dependency. To explore variation in Si NM benefits on plants, we conducted a meta-analysis of 51 independent studies conducted worldwide. We found that Si NM addition overall increased antioxidant enzyme activities (16.3%), antioxidant metabolite contents (15.2%) and defence-related gene expression (178.2%), overall decreasing oxidative stress in plant by 24.0%. These effects varied depending on several factors such as application dose, application duration and application method. Moreover, we observed that Si NM-mediated effects on plant physiology could last several weeks, but this depended on the application dose of Si NMs. Therefore, we conclude that Si NMs could be further developed as an efficient and environmentally-friendly alternative to synthetic agrochemicals for plant stress mitigation.